Ultrasound combined with microbubble enhanced renoprotective effects of NLRP3 inflammasome inhibitor MCC950 in CKD model - Wen, Wen; Tu, Bin; Ren, Xiaomei; Liu, Yangli; Jiang, Rufang; Wu, Xiaofeng; Liu, Jian (Frontiers in Pharmacology, 2025)
ObjectiveThis study evaluated the effectiveness of the NLRP3 inflammasome inhibitor MCC950 combined with ultrasound (US) and microbubbles (MBs) on kidney function and fibrosis in a rat model of chronic kidney disease (CKD).MethodsAfter establishing the model, SD rats were divided into eight groups (n = 5): Control, CKD, MCC950 (10 mg/kg), MCC950 (5 mg/kg), US + MCC950 (5 mg/kg), US + MBs + MCC950 (5 mg/kg), US and US + MBs. MCC950 was administered at high (10 mg/kg) or low (5 mg/kg) doses, and 200 μL of sulfur hexafluoride microbubbles was delivered via tail vein injection. Ultrasound (mechanical index 0.99) was applied over the kidneys for 10 min every 2 days for six sessions post-injection. Renal function was assessed from urine and blood samples. Kidney tissues were examined using HE and Masson staining, while mRNA and protein levels of NLRP3, caspase-1, ASC, IL-1β, and IL-18 were quantified via RT-qPCR, immunohistochemistry, and ELISA.ResultsTreatment with MCC950 (10 mg/kg), US + MCC950 (5 mg/kg), and US + MBs + MCC950 (5 mg/kg) significantly reduced serum creatinine, blood urea nitrogen, and albumin-to-creatinine ratios, and alleviated kidney damage and fibrosis compared to untreated CKD rats. Notably, US + MBs + MCC950 (5 mg/kg) was as effective as 10 mg/kg MCC950 treatment, with US + MBs further enhancing MCC950’s inhibitory effects on NLRP3 inflammasome activity in renal tissues, manifesting as reductions in the mRNA and protein expression of NLRP3, caspase-1, ASC, IL-1β and IL-18.ConclusionThe combination of US and MB therapy with MCC950 improves renal function and reduces fibrosis in CKD rats, providing promising evidence for its potential in renal protection and the treatment of inflammatory disorders.